Suppression of Vestibulo-Ocular Reflex With Increased Mental Workload While Driving - Takuya Kono; Yuki Sato; Takahiro Wada; Daichi Tsunemichi; Naoyuki Fujiyama; Yoshiki Ono (IEEE Access, 2023)
An excessive mental workload (MWL) of drivers can cause traffic accidents. Previous studies have proposed an increased MWL indicator based on the vestibulo-ocular reflex (VOR), a reflexive eye movement opposite to the head movement, and demonstrated that the VOR modeling error (i.e., difference between the eye movements estimated by a VOR model and the actual eye movements) increases with increased MWL while driving. However, without the VOR model, the association between increased MWL and changes in VOR such as VOR suppression or promotion remains unclear. Our objective was not to quantify the absolute MWL, but to investigate the association between heightened MWL during driving and variations in the VOR gain (i.e., the ratio of eye to head angular velocities). Additionally, we examined an auxiliary VOR parameter linked to self-motion estimation, which accommodates the alteration in VOR gain. An experiment involving twelve participants driving along a straight road with and without an additional mental task was conducted. A Wilcoxon signed-rank test revealed a significant decrease in the VOR gain under high MWL, indicating that VOR suppression is associated with increased MWL. Using the VOR gain simplifies the increased MWL indicator without optimizing the VOR model parameters for each driver. Furthermore, the reduced self-motion estimation parameter under high MWL may enhance our understanding of the VOR suppression mechanism. In the future, we will determine how an increased MWL at different cognitive task intensities is associated with the VOR gain or decreased driving performance.